TOTO, positioning plumbing products globally - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
TOTO is the world's largest manufacturer of toilets. It holds its position based on beliefs about company innovations combined with an emphasis on sustainability. This case discusses the firm's international marketing practices and the ethical guidelines that it follows.